POLITICAL AND HISTORICAL RELATIONS OF PATANI KINGDOM IN THAILAND AND PATANI VILLAGE IN INDONESIA - Tajuddin, Muhammad Saleh; Yeyeng, Andi Tenri; Natsir, Muh.; Hasyim, Ahmad (JPP (Jurnal Politik Profetik), 2022)
This paper discusses the historical and political relations of the Patani Kingdom in Thailand and Patani in Takalar Regency, Indonesia. These two Patani had strong ties related to historical and political issues. This research uses qualitative methods with observational data collection techniques, interviews and documentation. Secondary data are obtained through textbooks, scientific journals, and online sources. The data were analyzed through the analysis of Miles and Haberman with the steps of data display, data verification and conclusions. This study found that the relationship between these two regions has occurred since 1634, where there was a massive exodus from Patani, Thailand to the Patani region in the Sanrobone Kingdom, Takalar, Indonesia due to the conflict that occurred between the Kingdom of Siam and the Kingdom of Patani in Thailand. Meanwhile, an important position in the politics of the Malays in Patani, Indonesia was as a royal clerk and harbormaster. On the other hand, the existence of the Bugis-Makassarese also had a political role in Patani, Thailand.